Deconstructing the indigenous in tourism : The production of indigeneity in tourism-oriented labelling and handicraft/souvenir development in Northern Europe - Keskitalo, E. Carina H.; Schilar, Hannelene; Heldt Cassel, Susanna; Pashkevich, Albina (Current Issues in Tourism, 2021)
In literature on tourism in northern or ‘Arctic’ areas and on regions and places in northern areas, terms such as ‘indigenous’ and ‘non-indigenous’ are often used to distinguish people and places from each other. The aim of this paper is to deconstruct the ‘indigenous’/‘non-indigenous’ categories as well as the geographical categories to which they are linked, using examples from tourism in northern Fennoscandia and northwest Russia, selected as areas with circumstances that vary greatly both locally and regionally. Specific focus is on the construction of labels and restrictions of use, particularly regarding handicrafts/souvenirs as a specific object of indigeneity to separate it from other objects. The study reviews the processes in tourism for constructing, labelling, and valuing – and thereby also exerting power upon – specific conceptions, and thereby also on the contesting of such processes amongst broader, but often unacknowledged, local groups.